GP73: the key to unlocking immunotherapies efficacy in solid tumors? - Alan L Parker; Rebecca J Bayliss (Journal for ImmunoTherapy of Cancer)
Resident Golgi protein 73 (GP73) is expressed in many healthy tissues, however overexpression is associated with both viral infections and cancer. As an oncoprotein, GP73 drives tumor progression and plays a fundamental role in immune regulation. A recent publication illustrates a role for GP73 in T-cell antitumor immunity employing GP73 genetically depleted T-cell mouse models. GP73-deficient T-cells were found to detrimentally affect CD8+T cell cytotoxicity and glycolysis primarily due to its interaction with Hypoxia-inducible factor 1α and mTOR levels in hypoxic cells, suggesting a key role for GP73 in T-cell cytotoxicity within the hypoxic tumor microenvironment. This finding opens the door to the potential development of GP73 targeting through ectopic expression of GP73 which was found to restore glycolysis and therefore T-cell cytotoxicity resulting in tumor regression. In addition, GP73 was found to be a potential biomarker to inform clinical treatment of patients undergoing immunotherapy. Could GP73 be the key to establishing a therapeutic strategy for generating improved patient responses to immunotherapy?